Antimicrobial Effect of a Peptide Containing Novel Oral Spray on Streptococcus mutans. (11th March 2020) - Xiong, Kaixin; Chen, Xuan; Hu, Hantao; Hou, Huihui; Gao, Peng; Zou, Ling
Abstract : Objective . To investigate the antibacterial effect of a novel antimicrobial peptide containing oral spray GERM CLEAN on Streptococcus mutans (S. mutans) in vitro and further explore the related mechanisms at phenotypic and transcriptional levels. Methods . The disk diffusion method was used to preliminarily appraise the antimicrobial effect of GERM CLEAN. The minimal inhibitory concentration (MIC) of GREM CLEAN towards S. mutans was determined by the broth dilution method. S. mutans virulence-related phenotypic assays including initial adhesive assay, pH drop, exopolysaccharides (EPS), and biofilm formation measurements and quantitative real-time PCR (qRT-PCR) were further applied to detect the inhibitory mechanisms of GREM CLEAN at 1/2MIC. Results . The diameter (10.18 ± 1.744 mm) of inhibition zones formed by GERM CLEAN preliminarily indicated its inhibitory effect on the major cariogenic bacteria S. mutans . The minimal inhibitory concentration of GERM CLEAN on S. mutans was 100% mass fraction (the stock solution). The study of the antibacterial mechanism showed that GERM CLEAN had a certain inhibitory effect on the initial adhesion, acid production, extracellular polysaccharides (EPS) production, and biofilm formation of S. mutans . GERM CLEAN disturbed S. mutans biofilm physiology mainly through destruction of biofilm architecture and suppression of bacterial growth. The results of qRT-PCR further confirmed that the expression levels of EPS and lactic acid generation genes including gtfB, gtfC, gtfD, and ldh were significantly repressed by treating with GERM CLEAN, and this was consistent with our phenotypic results. Conclusion . The novel antimicrobial peptide containing oral spray GERM CLEAN has an anti- Streptococcus mutans effect and the inhibitory property may be due to suppression of the virulence factors of S. mutans including adhesive, acidogenicity, EPS, and biofilm formation.